Examining the Geologic Link of Arsenic Contamination in Groundwater in Orange County, North Carolina - Dinwiddie, Ethan; Liu, Xiao-Ming (Frontiers in Earth Science, 2018)
Ingestion of inorganic arsenic through food and water can have severe adverse health effects on the human body. Therefore, government regulations and health guidelines for arsenic concentrations in water have been established around the world to avoid or mitigate these health effects. In recent decades, analysis of groundwater in many locations around the world have revealed arsenic concentrations that exceed government regulation levels. The section of the Carolina Terrane located in North Carolina is one of such recently discovered areas. This study investigates the relationship between the geologic units of the Carolina Terrane and arsenic concentrations in well water samples in Orange County, North Carolina. Kriging interpolation mapping and multivariate analysis reveals spatial and geochemical connections between wells of detectable arsenic and the "Neoproterozoic epiclastics" unit and geochemical variables such as F-, pH, and alkalinity. These associations imply that arsenic in Orange County, NC is being mobilized from authigenic arsenic-bearing sulfide minerals in the "Neoproterozoic epiclastics" bedrock unit by oxidative release likely associated with increased F-, pH, and alkalinity.